Trinucleotide Repeat Protocols - Kohwi, Yoshinori.; Kohwi, Yoshinori.; McMurray, Cynthia T.; McMurray, Cynthia T. (Methods in Molecular Biology, 2013)
Two decades have passed since trinucleotide repeat expansion was first discovered in genes responsible for certain neurological diseases. Since then, new technologies have developed and innovative concepts have emerged, which may prove useful in devising therapeutic approaches to neurological diseases. Divided into six convenient sections, Trinucleotide Repeat Protocols, Second Edition covers a wide range of topics such as an overview of trinucleotide repeat diseases, synaptic plasticity, embryonic stem (ES) cell-related protocols with a focus on HD, RNA-related protocols, and analysis of epigenetic modification in fragile X syndrome.  This edition focuses not only on direct analysis of trinucleotide repeat diseases but also on alternative approaches for the analysis of trinucleotide repeat diseases, with the hope that this will result in a better understanding of the mechanisms and future therapeutic prospects for treatment of these diseases. Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Trinucleotide Repeat Protocols, Second Edition seeks to serve researchers with its thorough methodologies on this expanding field.